Serotonergic Regulation of Hepatic Energy Metabolism - Jiwon Park; Wooju Jeong; Chahyeon Yun; Hail Kim; Chang-Myung Oh (Endocrinology and Metabolism, 2021)
The liver is a vital organ that regulates systemic energy metabolism and many physiological functions. Nonalcoholic fatty liver disease (NAFLD) is the commonest cause of chronic liver disease and end-stage liver failure. NAFLD is primarily caused by metabolic disruption of lipid and glucose homeostasis. Serotonin (5-hydroxytryptamine [5-HT]) is a biogenic amine with several functions in both the central and peripheral systems. 5-HT functions as a neurotransmitter in the brain and a hormone in peripheral tissues to regulate systemic energy homeostasis. Several recent studies have proposed various roles of 5-HT in hepatic metabolism and inflammation using tissue-specific knockout mice and 5-HT-receptor agonists/antagonists. This review compiles the most recent research on the relationship between 5-HT and hepatic metabolism, and the role of 5-HT signaling as a potential therapeutic target in NAFLD.